2022
DOI: 10.47654/v26y2022i2p26-47
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Authentic Leadership and Work Engagement on Turnover Intention The Moderating Role of Job Satisfaction and Organizational Size

Abstract: This study attempts to give further complete theoretical literature and managerial level on authentic leadership and its impact on work engagement and turnover intentions, utilizing job satisfaction as a moderator. However, the objectives of this study findings can help a better understanding about how leaders and workers can assist lower turnover intentions and, as a result, build tools, programs, and policies to assist these critical actions.Design/Methodology/Approach: This study included 43 items of questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Traditional employee turnover theories tend to analyze and compare only a small portion of employee data, and cannot fully analyze the collected employee information data comprehensively, which may lead to inaccurate results and cause companies to make wrong decisions in the end [ 6 , 7 ]. At the same time, there is a large amount of unbalanced data with widely varying sample sizes in real life, such as medical pathology diagnosis, credit card fraud, network intrusion information, business operations and employee turnover data [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional employee turnover theories tend to analyze and compare only a small portion of employee data, and cannot fully analyze the collected employee information data comprehensively, which may lead to inaccurate results and cause companies to make wrong decisions in the end [ 6 , 7 ]. At the same time, there is a large amount of unbalanced data with widely varying sample sizes in real life, such as medical pathology diagnosis, credit card fraud, network intrusion information, business operations and employee turnover data [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, most companies pay more attention to questionnaire research and information collection for employees. Therefore, analyzing employee data through SVM algorithm and building employee turnover model with existing samples can more effectively enable companies to detect employee turnover earlier [ 7 , 10 ]. There are many mature SVM algorithms that have very good classification results when facing balanced samples.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, empirical data from various studies established the link between authentic leadership and work engagement. For example, employees' perception of authentic leadership positively affects their perception of work engagement (Anantha et al, 2022). As a result, the following hypothesis has been advanced: H2: The authentic leadership has positive significant effects on work engagement.…”
Section: Authentic Leadership and Work Engagementmentioning
confidence: 99%
“…This hypothesis focus on studying the effect of authentic leadership using its dimensions (self-awareness, relational transparency, balanced processing, and internalized moral perspective) as an independent variable on academic staff performance. Such as (Kurian & Nafukho, 2022;Arokiasamy et al, 2022 ;Nawaz & Tian, 2022;Duarte et al, 2021;Llorens et al, 2021;Astuti et al, 2020;Soares & Lopes, 2020 ;Supriyadi et al, 2020;Aropah & Sumertajaya, 2020;Asbari et al, 2019;Alzghoul et al, 2018;Ahmad et al, 2015) previous studies indicated that authentic leadership affect on academic staff performance. Accordingly, the first main hypothesis states: H1: "There is a statistically significant effect of authentic leadership on academic staff's performance in Upper Egypt Universities " This hypothesis has four relevant sub-hypotheses:…”
Section: Hypothesis Onementioning
confidence: 99%